Exploring the adoption of beneficial management practices on leased first nations agricultural lands: a modelling approach for integrated nitrogen management - Ampomah, Samuel; Arcand, Melissa; Natcher, David (Frontiers in Sustainable Food Systems, 2025)
In Canada, beneficial management practices (BMP) are being used to reduce agricultural greenhouse gas emissions, manage environmental risks, and contribute to national climate goals. A key component of BMP is effective nitrogen (N) fertilizer management, which is essential for improving both soil health and economic profitability and reducing environmental risk. This research employed a modelling approach to evaluate the potential adoption of BMPs related to nitrogen fertilizer management in canola production on agricultural lands on the Mistawasis Nêhiyawak First Nation (MNFN) reserve in central Saskatchewan. The MNFN lands have a unique historical and cultural perspective, where systemic barriers to modern agricultural adoption have limited participation of local farmers and shifted agricultural decision making to non-Indigenous farmers who rent Indigenous governed lands—a common arrangement across most First Nations in the region. The modelling exercise serves as a starting point for engaging with tenant farmers on future nitrogen management strategies that more closely reflect community values and desired outcomes for their lands, including the balance of economic viability with environmental stewardship. Two distinct fertilizer application scenarios were simulated: inorganic nitrogen fertilizer and the integrated use of organic and inorganic fertilizers as BMP for canola yield. Results indicate that the combined approach within the context of the integrated nitrogen management regime could increase crop yields. The economic evaluation highlighted the financial viability of nitrogen management BMPs, leading to higher net present values (NPV). Sensitivity analysis revealed the impact of market fluctuations on economic indicators, particularly prices and costs, indicating that BMPs offered greater resilience against price volatility and rising input costs. This study contributes to ongoing efforts to improve nitrogen fertilizer practices in the region and to facilitate adoption of BMPs, particularly on First Nation reserves in Canada, with spillover benefits for the Canadian agricultural sector.